Polyfunkční dům - Hirt, Lukáš (Vysoké učení technické v Brně. Fakulta stavební, 2015)
V diplomové práci řeším novostavbu polyfunkčního domu. Objekt se bude nacházet ve městě Brno-Horní Heršpice, Sokolova ulice, parcela č. 707/1, okres Brno. Polyfunkční dům je čtyřpodlažní. Rozměry v maximálním opsaném obrysu budovy jsou 20.56x21.06m. Výška atiky je 12.815m nad 0. Budova je postavena na základových pasech z prostého betonu C20/25. Betonová deska je vyztužena kari sítí 150x150x6. Objekt je navržen ze systému KM Beta Sendwix. Prefabrikované chodiště je ze železobetonu. Stropy jsou řešeny stropními panely Spiroll. Střecha nad kavárnou a byty je plochá s povlakovou krytinou.

I deal with new building of multi-functional building. The building will be located in the town Brno-Horni Herspice, Sokolova street, parcel number 707/1, Brno district. Multi-functional building has four floors. Maximum dimensions the outline of the building are 20.56X21.06m. Height of the parapet wall is 12.815m above 0. The building is build on foundation strips of plain concrete 20/25. Concrete slab is reinforce with kari net 150x150x6. The building is designed from the masonry system Sendwix. The precast staircase is made of reinforced concrete. Ceilings are designed of the floor slabs Spiroll. Roof above cafe and flats is flat with coating covering.
Multi-functional Building
Keywords: polyfunkční dům; plochá střecha; bytové jednotky; kavárna; základové betonové pasy; zdící systém Sendwix; stropní panel Spiroll; železobetonové schodiště; povlaková krytina; multi-functional building; flat roof; apartments; cafe; concrete foundation strips; masonry systém Sendwix; precast floor slab Spiroll; reinforced concrete staircase; coating covering